Abstract 132: Angioplasty and Stenting for Symptomatic Vertebral Artery Atherosclerotic Disease: A Systematic Review and Meta‐Analysis - Mehdi C. Bouslama; Andre Monteiro; Brianna Donnelly; Cathleen Kuo; Hannah Danziger; Silvia Hugec; Jaims Lim; Ryan C. Turner; Kunal P. Raygor; Ammad Baig; Rosalind Lai; Kenneth V. Snyder; et al. (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Vertebral artery stenting represents a viable option in treating symptomatic vertebral artery atherosclerotic stenosis. However, its safety and efficacy in improving neurological status and reducing recurrent strokes remain to be established. Methods We systematically searched PubMed, Embase, and Cochrane databases using keywords with Boolean operators to increase search sensitivity and specificity (‘extracranial’; ‘stenting’; ‘vertebral artery’; ‘stenosis’). We included articles reporting patients > 18 years old with symptomatic extracranial vertebral artery stenoses due to atherosclerosis treated with stenting (with or without angioplasty). Those reporting patients with vertebral dissections were excluded. Patients’ characteristics, procedural details, complications, and outcomes were extracted. Estimated rates weighted for sample size were generated for each variable using fixed and random effects models. Results From 89 unique studies identified, 21 met our inclusion criteria and were included in the analysis, comprising 1499 patients with 1570 lesions. The mean age was 65 years, and 74.4% were men. The mean baseline NIHSS was 4.6. The most frequent stenosis location was the V1 segment of the vertebral artery (88.4%). Device‐related issues occurred in 1.8%. Periprocedural ischemic and hemorrhagic complications occurred in 2.1% and 1.7%, respectively. Neurological improvement post‐procedure was observed in 84.2%, and the in‐hospital mortality rate was 2.1%. During follow‐up, in‐stent stenosis >50% was observed in 12.8%, and retreatment with either re‐stenting or angioplasty was performed in 10.8%. Ischemic complications during follow‐up occurred in 5%, and the overall mortality rate was 5%. Conclusion Stenting for the treatment of atherosclerotic vertebral artery stenosis is technically feasible, associated with a high rate of neurological improvement and low short and long‐term complication rates.